Analisis Etika Deskriptif Pada Cerpen “Telunjuk” Karya Eli Rusli: Etika Deskriptif pada Cerpen "Telunjuk" Karya Eli Rusli - rino, Jeki suga (ESTETIKA: JURNAL PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2024)
ABSTRACT This study will analyze short stories with a descriptive ethical approach. Descriptive ethics describes the good and bad moral behavior of an action. Nowadays there are many cases of people's moral behavior that deviate from the prevailing norms. Corruption, murder, fraud and others are a form of deviant social behavior. We can learn people's behavior through literary media, one of which is short stories. Short stories are short stories that contain real people's behavior, experiences and imagination of the author. This research will describe the character's moral behavior in Eli Rusli's short story "Telunjuk" using a descriptive ethical approach. This study uses a qualitative method. The use of this method is very suitable in analyzing a word or language with the subjective assessment needs of the researcher. This study uses documentation techniques because the research data is in the form of the publication of the short story Telunjuk on the media of the Mind of the People newspaper. Research data will be analyzed with a descriptive ethical theory approach. The results of the research show that there is bad behavior from the characters in the short story. Behavior in utilizing a position for personal gain. In addition, there are good figures at work, even though they are high positions and do not take advantage of these positions for personal gain. Keywords: Descriptive ethics, short stories, characters, good and bad, behavior.